Temptation, Willpower, and the Problem of Rational Self-Control - MARY E. DEILY; W. ROBERT REED (Rationality and Society, 1993)
This article develops a model of consumption when individuals maximize utility knowing that they will experience varying levels of temptation and willpower over time. Examination of the optimal consumption path reveals that consumers may resist temptation by altering their consumption path. This can generate consumption patterns that mimic time preference even when no underlying time preferences exist. Self-control strategies to increase consumer welfare, such as precommitment and public side bets, are shown to derive directly from the model.